Analisis Kaidah Metode Pembelajaran Al-Qur’an Dalam Pendidikan Islam - Alexa Ayu Dewanda; Chadiza Azzahra Lubis; Hanestesia Zahara; Resya Eka Putri; Wismanto Wismanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
A method is a set of methods or methods used by teachers in learning so that students can achieve certain learning goals and skills. Many verses in the Al-Qur’an explain the use of methods in teaching. Some of them we find in Surah Ali Imran 159 and Al-Maidah 67. This research uses a qualitative descriptive method with a literature review. The purpose of this research is to determine the method of learning or teaching the Al-Qur'an. Based on the discussion, the teaching methods of the Al-Qur’an are (1) Hiwar, which is an alternating conversation between two or more parties through questions and answers regarding a topic leading to a goal, and (2) Tabligh, which is a systematic, orderly and measurable method used by preachers in presenting tabligh material to their audience.